ገበታ: የአየር ለውጥን መቋቋም ስለሚችሉ የተሻሻሉ የእንስሳት መኖ ቴክኖሎጂዎች የራዲዮ ፕሮግራም፡ ክፍል ሰባት - International Livestock Research Institute (International Livestock Research Institute, 2022)
In episode seven, which aired on Debre Birhan Fana FM 94.0 on 2 August 2022, ILRI's Kindu Mekonnen and Melkamu Bezabih discussed the benefits of improved feeding troughs and sheds to minimize feed wastage, improve feed intake and ease animal handling. This radio program series is produced by Africa RISING and AICCRA as part of the partnership – Use of interactive radio to scale-up feed and forage innovation technologies in Ethiopia.